2022
DOI: 10.1038/s41598-022-09828-z
|View full text |Cite
|
Sign up to set email alerts
|

Genomic evaluation of hybridization in historic and modern North American Bison (Bison bison)

Abstract: During the late nineteenth century North American bison underwent a significant population bottleneck resulting in a reduction in population size of over 99% and a species-level near-extinction event. Factors responsible for this destruction included indiscriminate killing, loss of access to suitable habitat, and diseases. At the nadir of this population crash, very few wild plains bison survived and were restricted to Yellowstone National Park, USA and a small number of wild wood bison remained in Wood Buffal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 42 publications
(49 reference statements)
1
17
0
Order By: Relevance
“…These findings suggest that the particular morphology of Jackie might be due to ancient introgressions of domestic dog alleles, that were almost completely eroded after a few backcrossing generations, leaving traces of dog ancestry only at particular genomic regions or in linkage with multiple or particular coat colour and other morphologically associated genes, and thus not detectable at the few uniparental and autosomal loci we analysed. Future genome-wide studies, based on ancestral chromosomal block reconstruction methods 49 , 50 could help identify possible dog-derived regions along Jackie's genome, potentially the reason for the observed morphological anomalies, as previously conducted in North American grey wolves to detect a functional 3-bp melanistic deletion along chromosome 16, presumably introgressed via historical admixture with dogs 51 , 52 , or in North American bison ( Bison bison ) populations to identify cattle haplotypes introgressed in their genomes over the last 200 years 53 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the particular morphology of Jackie might be due to ancient introgressions of domestic dog alleles, that were almost completely eroded after a few backcrossing generations, leaving traces of dog ancestry only at particular genomic regions or in linkage with multiple or particular coat colour and other morphologically associated genes, and thus not detectable at the few uniparental and autosomal loci we analysed. Future genome-wide studies, based on ancestral chromosomal block reconstruction methods 49 , 50 could help identify possible dog-derived regions along Jackie's genome, potentially the reason for the observed morphological anomalies, as previously conducted in North American grey wolves to detect a functional 3-bp melanistic deletion along chromosome 16, presumably introgressed via historical admixture with dogs 51 , 52 , or in North American bison ( Bison bison ) populations to identify cattle haplotypes introgressed in their genomes over the last 200 years 53 .…”
Section: Discussionmentioning
confidence: 99%
“…In the simulation test, only limited number of the reads (∼0.2%) in the in silico datasets of each species have been mapped to the other genome (Table ). The gene introgression between bison and cattle in North America has been clarified in recent research . It is possible that the beef sample we used here was from a species with genetic variants originating from gene introgression which has been accumulated to a certain level during propagation.…”
Section: Resultsmentioning
confidence: 99%
“…The gene introgression between bison and cattle in North America has been clarified in recent research. 40 It is possible that the beef sample we used here was from a species with genetic variants originating from gene introgression which has been accumulated to a certain level during propagation. This observation indicated that in a practical test, the choice of reference genomes in a read mapping-based analysis would impact both the identification and quantification of an ingredient.…”
Section: Validating the Data Analysismentioning
confidence: 99%
“…3 and 6 ). Thus, it is feasible that the presence of these gene segments in bison is a consequence of cattle introgression following hybridization between bison and cattle in the late 1800s (Stroupe et al 2022 ). However, we located ultralong-encoding IGHV in all members of the Bos and Bison group, including Bos frontalis , which is evolutionary older than bison, and Bos primigenius , the ancestor to extant taurine ( Bos taurus ) and zebu ( Bos indicus ) cattle that went extinct in the early 1600 s (Zeyland et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%